2022
DOI: 10.3390/antibiotics11020135
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: Biological Activities and Modern Pharmaceutical Forms

Abstract: Curcumin (1,7-bis-(4-hydroxy-3-methoxyphenyl)-hepta-1,6-diene-3,5-dione) is a natural lipophilic polyphenol that exhibits significant pharmacological effects in vitro and in vivo through various mechanisms of action. Numerous studies have identified and characterised the pharmacokinetic, pharmacodynamic, and clinical properties of curcumin. Curcumin has an anti-inflammatory, antioxidative, antinociceptive, antiparasitic, antimalarial effect, and it is used as a wound-healing agent. However, poor curcumin absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(98 citation statements)
references
References 206 publications
(168 reference statements)
0
98
0
Order By: Relevance
“…Cur has been discovered to have a variety of biological and anticancer activities, including antibacterial, antioxidant, and anti-inflammatory [ 23 ]. Curcumin has been studied for its ability to alleviate various cancers, including colon, and breast cancer [ 24 ]. Its anticancer and antioxidant properties have been widely used in clinical trials in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Cur has been discovered to have a variety of biological and anticancer activities, including antibacterial, antioxidant, and anti-inflammatory [ 23 ]. Curcumin has been studied for its ability to alleviate various cancers, including colon, and breast cancer [ 24 ]. Its anticancer and antioxidant properties have been widely used in clinical trials in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolites formed include curcumin glucuronide and curcumin sulfate, which are found in the urine on oral administration of curcumin. Dihydrocurcumin glucuronide, tetrahydrocurcumin glucuronide, and hexahydrocurcumin are found in the bile [30,35,36]. Pandey et al [37] found that most of the metabolites of curcumin are found in feces during oral and intraperitoneal administration.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin (1,7-bis-(4-hydroxy-3-methoxyphenyl)-hepta-1,6-diene-3,5-dione) is a yellow–orange lipophilic compound that dissolves in acetone, dimethylsulfoxide, and ethanol but is insoluble in water, acidic, and neutral solutions. This compound is an integral component of turmeric ( Curcuma longa ) (up to ~ 5%) [ 22 ]. This aromatic ginger family ( Zingiberaceae ) plant is native to southwestern and southern Asia [ 22 ].…”
Section: Methodsmentioning
confidence: 99%